26 Improving timeliness of specialist referral and diagnosis for patients with suspected lung cancer through standardization. (25th November 2019) - Golemiec, Breanne; Mullin, Monica LL; Tran, Audrey; Noseworthy, Christine; Stone, Christopher JL; Howard, Thomas; Dhillon, Gurmohan Rob; Parker, Christopher M; Digby, Geneviève C
Abstract : Background: Delays in lung cancer (LC) diagnosis are associated with worse clinical outcomes. Our rapid assessment LC clinic identified referral delays following thoracic imaging suspicious for LC and delays associated with unstructured triage. Objectives: Decrease time from suspicious CT chest to LC clinic referral and decrease time from referral to diagnosis and staging. Methods: Retrospective baseline chart review (Jan–Apr 2018) and prospective monitoring (May 2018–May 2019). PDSA cycles: 1) Standardized Triage Pathways (nurse-physician triage to diagnostic pathways, pre-ordered staging tests, small nodule clinic); 2) local standardization and regional implementation of CT reporting recommending LC clinic referral (March 2019). Data include dates of: imaging suspicious for LC, CT chest, specialist referral and assessment, staging tests, radiologist recommendations and diagnosis. Data are reported as mean days; statistical process control XbarS charts and unpaired t-tests were used to assess for significance. Results: Following PDSA 1, there were reductions in mean time from referral to PET (40.5 to 27.3 days), to CT/MRI Brain (35.8 to 18.8 days), and to diagnosis (41.4 to 30.1 days), all significant by special cause variation. Following PDSA 2, the percentage of LC clinic patients with a CT chest recommending clinic referral increased (25.2% to 37.0%, p=0.041), with increased recommendations from regional hospitals (4.2% to 16.5%, p=0.022). When a radiologist recommended LC clinic referral, time to referral and assessment were faster (7.3 vs. 15.5 days, p=0.0001; 20.3 vs. 26.2 days, p=0.001, respectively). Conclusions: Standardization of radiologist reporting and LC clinic triage led to significant improvement in timeliness of specialist access, diagnosis and staging investigations.